Effects of upper extremity blood flow restriction training on muscle strength and hypertrophy: a systematic review and meta-analysis - Jing, J.; Zheng, Q.; Dong, H.; Wang, Y.; Wang, P.; Fan, D.; Xu, Z. (Frontiers in Physiology, 2025)
Background: Low load resistance training with blood flow restriction (LL-BFRT) has been shown to improve muscle strength and hypertrophic function. The effect of LL-BFRT on lower extremity muscle improvement has been widely discussed. However, no studies have discussed the effect of this training method on the upper extremity muscles until now. This systematic review and meta-analysis focused on the use of LL-BFRT in the upper extremity muscles.